Impacts of long-standing illness and chronic illness on working hours and household income in a longitudinal UK study - Cara L. Booker; Leanne Andrews; Gillian Green; Meena Kumari (Elsevier, 2020)
Individuals within households encounter a variety of events including development of a disability or chronic illness. We used data from the Understanding Society, 2009-2016, to determine whether there are changes to working hours or household income as a result of an individual developing an illness. After adjusting for a variety of sociodemographic characteristics, there were few associations observed between one's own individual illness status and household income. There was a clear trend of reduction of weekly working hours with increasing severity and chronicity of the individuals' illness or disease. Individuals who were not ill, but lived in an household with an ill person worked about 30-min less per week, b = −0.69, 95% confidence interval (CI)=(-1.09, −0.30), while those with a limiting long-standing illness and a chronic disease worked 3.5 h less per week, b = −3.64, 95% CI=(-4.21, −3.08), compared to individuals with no illness in their household. Individuals with a limiting illness only had lower incomes, b = −0.04, 95% CI=(-0.07, −0.004) compared to individuals with no household illness. These associations were not greatly changed with the inclusion of reception of benefits or being cared for. Interactions were observed by gender, age being cared for and reception of benefits. Additionally, there were differences were observed by working age groups and between those who lived alone and those who did not. The findings suggest that while there is a reduction of working hours among individuals with an illness or who have an ill person in their home, household income is resilient to the experience of an illness, in the United Kingdom. However, this appeared to differ by household composition, i.e. whether individuals were of working age or whether they lived alone. Identification of households at highest risk of income reduction may serve to inform policy and appropriate distribution of services and support.